“Marketing in the Age of GenAI and Social Commerce: Current Trends, Strategic Implications, and a Research Publication Proposal” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper reviews and synthesizes current trends shaping marketing practice in 2024–2025, with a focus on generative AI (GenAI), hyper-personalization, social commerce, creator/influencer strategies, privacy-driven data governance, and sustainability-driven branding. Drawing on industry reports and recent scholarship, the paper: (1) maps the major forces reshaping marketer decision-making; (2) proposes a conceptual framework that links technological adoption (GenAI + analytics) to customer-centric outcomes (personalization, engagement, conversion); and (3) outlines a mixed-methods research design to empirically test that framework across B2C retail and D2C settings. Practical implications, managerial guidelines, limitations, and directions for future research are provided. The work is written and formatted for submission to marketing journals that accept applied-conceptual manuscripts.